CGI technologies and methods for 3D scanning – new horizons - Yakimov, Petko (Yearbook Telecommunications, 2021)
The enduring presence of photometric technology and in particular Lidar 3D scanning systems in CGI’s technological tools testify to the potential and development opportunities they possess. But here we will focus on another quality of technology. The opportunities they provide for achieving new visual forms by interpreting nature on the basis of basic features. for direct work and manipulation of raw point clouds massif. The reason - a non-standard visual method for interpreting reality offering an extremely wide range of transformations even in the direction of algorithmic structural modeling. In this article, we will analyze both the tools and the technological practices known to us as "technological hybrids".